Videolaryngoscope-assisted fibreoptic tracheal intubation in a young adolescent with hunter syndrome for posterior cervical fusion. - Zabir, AF; Frawley, G; Squire, P (Department of Surgery, UKM Medical Centre, 2013)
We here describe a videolaryngoscope assisted fibreoptic tracheal intubation in a 17-year-old patient with Hunter Syndrome (Mucopolysaccharidosis Type II) and known difficult intubation who required posterior cervical fusion surgery for cervical canal stenosis. The patient had a history of failed nasal and oral fibreoptic intubation. The use of a videolaryngoscope enabled continuous visualization of the tracheal inlet and allowed a straightforward nasal fibreoptic intubation attempt without complications. This report suggests a viable alternative for the management of a known difficult airway in children with mucopolysaccharidosis.